2010
DOI: 10.1016/j.rbmo.2010.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone supplementation improves implantation and pregnancy productivity rates for poor-prognosis patients undertaking IVF

Abstract: In a sequential crossover study of IVF conducted from 2002 to 2006, growth hormone (GH) supplementation was assessed in poor-prognosis patients, categorized on the basis of past failure to conceive (mean 3.05 cycles) due to low response to high-dose stimulation (<3 metaphase II oocytes) or poor-quality embryos. Pregnancy rates in both fresh and frozen transfer cycles and the total productivity rates (fresh and frozen pregnancies per egg collection) were compared. In all, 159 patients had 488 treatment cycles: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
70
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 37 publications
(44 reference statements)
8
70
1
3
Order By: Relevance
“…However, the exact mechanism through which GH action regulates oocyte mitochondrial function remains to be elucidated, along with considerations related with the GH dosage; in this study being either 1 IU or 2.5 IU daily. Nevertheless, we can thus confirm that the administration of exogenous GH supplements, in conjunction with standard ovarian stimulation regimens, does indeed improve the quality of human oocytes, as demonstrated previously (Yovich & Stanger 2010), via a potential enhancement in mitochondrial functionality. With respect to older women, improvements in pregnancy rates have been clearly (b) Assessment of mitochondrial membrane integrity, based on cytochrome c oxidase immunolabelling.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…However, the exact mechanism through which GH action regulates oocyte mitochondrial function remains to be elucidated, along with considerations related with the GH dosage; in this study being either 1 IU or 2.5 IU daily. Nevertheless, we can thus confirm that the administration of exogenous GH supplements, in conjunction with standard ovarian stimulation regimens, does indeed improve the quality of human oocytes, as demonstrated previously (Yovich & Stanger 2010), via a potential enhancement in mitochondrial functionality. With respect to older women, improvements in pregnancy rates have been clearly (b) Assessment of mitochondrial membrane integrity, based on cytochrome c oxidase immunolabelling.…”
Section: Discussionsupporting
confidence: 81%
“…A growing body of evidence, in both human and animal models, suggests that GH is an important regulator of ovarian steroidogenesis (Nakamura et al 2012), follicular development (Bachelot et al 2002) and oocyte maturation (Bevers & Izadyar 2002). In clinical application, we have recently demonstrated that GH supplementation together with gonadotropin-induced ovarian stimulation has lead to significant improvement in oocyte quality (Yovich & Stanger 2010). However, it is not yet clear how GH exerts its action on human oocytes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations